SEJARAH DAN PERAN MASJID MANTINGAN DALAM PENYEBARAN ISLAM DI JEPARA - Rohmaniah, Alfiatur (ADDABANA: Jurnal Pendidikan Agama Islam, 2024)
Abstract: The Mantingan Mosque, a historical landmark in Jepara, Central Java, plays a central role in the spread of Islam in the region. Through this study, we can better understand the important role of Mantingan Mosque in the history of the spread of Islam in Jepara and the cultural values that continue to be upheld to this day. This study uses primary and secondary data collection methods from three sources, namely observations of the Mantingan Mosque, interviews with the chairman of the mosque foundation, and literature studies. This study uses 4 stages of historical methods, namely heuristics, criticism, interpretation and historiography. This article aims to provide a deeper understanding of how this mosque became a center of religious activities, and an important pilgrimage destination for the community. In addition, this article also aims to highlight the architectural value and cultural acculturation contained in the Mantingan Mosque, as well as its positive impact on the economy and social life of the surrounding community. Based on the results of this study, the Mantingan Mosque was built by Queen Kalinyamat in 1559, this mosque is not only a center of worship, but also a symbol of political and religious power in its time. With architecture that reflects the acculturation of Islamic, Javanese, Chinese, and Hindu-Buddhist cultures, the Mantingan Mosque has become a religious tourism destination that is visited by thousands of people every year. Its existence has a positive influence, namely by coming to the Mantingan Mosque they are people of faith. As the center of Islamic civilization in Jepara, the Mantingan Mosque has a positive impact on the economy and life of the surrounding community. With the religious and historical values contained in it, this mosque is a valuable heritage that must be preserved and maintained for future generations.Keywords: History and Role, Jepara, Mantingan Mosque. Abstrak: Masjid Mantingan, sebuah landmark bersejarah di Jepara, Jawa Tengah, memegang peran sentral dalam penyebaran Islam di wilayah tersebut. Melalui penelitian ini, kita dapat lebih memahami peran penting Masjid Mantingan dalam sejarah penyebaran Islam di Jepara dan nilai-nilai budaya yang terus dijunjung tinggi hingga saat ini. Penelitian ini menggunakan metode pengumpulan data primer dan sekunder dari tiga sumber yaitu observasi masjid Mntingan, wawancara dengan ketua Yayasan masjid, dan studi literatur. Pada penelitian ini menggunakan 4 tahap metode sejarah, yakni heuristik, kritik, interpretai dan historiografi. Artikel ini bertujuan untuk memberikan pemahaman yang lebih dalam tentang bagaimana masjid ini menjadi pusat kegiatan keagamaan, dan destinasi ziarah yang penting bagi masyarakat. Selain itu, artikel ini juga bertujuan untuk menyoroti nilai arsitektur dan akulturasi budaya yang terkandung dalam Masjid Mantingan, serta dampak positifnya terhadap ekonomi dan kehidupan sosial masyarakat sekitar. Berdasarkan hasil penelitian ini Masjid Mantingan dibangun oleh Ratu Kalinyamat pada tahun 1559, masjid ini tidak hanya menjadi pusat ibadah, tetapi juga simbol kekuatan politik dan keagamaan pada zamannya. Dengan arsitektur yang mencerminkan akulturasi budaya Islam, Jawa, Tionghoa, dan Hindu-Buddha, Masjid Mantingan menjadi destinasi wisata religi yang ramai dikunjungi oleh ribuan orang setiap tahunnya. Keberadaannya memberikan pengaruh positif yaitu dengan datang ke masjid Mantingan mereka adalah orang-orang yang beriman.  Sebagai pusat peradaban Islam di Jepara, Masjid Mantingan memberikan dampak positif terhadap ekonomi dan kehidupan masyarakat sekitar. Dengan nilai-nilai keagamaan dan sejarah yang terkandung di dalamnya, masjid ini menjadi warisan berharga yang harus dilestarikan dan dijaga untuk generasi mendatang.Kata Kunci: Jepara, Masjid Mantingan, Sejarah dan Peran.